The value of textual haptic information in online clothing shopping - Rodrigues, Tomé (2017)
Purpose: The purpose of this paper is to evaluate the potential of textual haptic information to minimize the effects of need for touch (NFT) in global online environments by testing the effect of hands on description on consumer perception and intention to purchase. Design/methodology/approach: The study was developed in three stages. A total of 140 valid responses were obtained in stage three. Multiple linear regression models and paired-samples t-test were applied to test the hypotheses. Findings: The results show that textual haptic information has a positive impact on consumers’ perception and on the intention to purchasing. Practical implications: To improve online sales firms should minimize the drawback of the inability of touching the product by providing textual haptic information. Originality/value: The findings are especially valuable since the number of studies assessing NFT in online apparel commerce is currently very limited. Thus, this study adds new empirical evidences to existent body of knowledge and could assist the development of global marketing strategies for increasing online fashion sales.